Blood donation during the coronavirus pandemic - Jawień, Wiktoria; Kądziołka, Anna; Kułaga, Daniela; Jurkiewicz, Beata (Health Promotion & Physical Activity, 2021)
Introduction: Despite years of research and scientific work, it has not yet been possible to produce such a valuable medication as blood. The pandemic does not reduce the need for blood, quite the opposite. However, due to the pandemic, the number of blood donors has dropped dramatically across the country. The aim of the study was to find out the opinions and attitudes of the respondents towards blood donation during the pandemic period and to assess their knowledge of the principles related to safe blood donation during this period. Material and methods: The study was conducted using a diagnostic survey method and the tool was our own research questionnaire. The study was conducted in February 2021, using Google Forms platform. In total, data were collected from 150 individuals (females: 60.6%, males 39.4%) aged between 16 and 73 years (mean 31.4 ± 12.4 years). Statistical analyses used a significance level of p = 0.05. Results: Nearly 39.7% of the respondents were regular blood donors, 12% of the respondents donated blood several times (12.3%). Blood was donated more often by men, people aged over 30 years, urban residents, and people with higher education (p < 0.001). Most people continued to donate blood despite the COVID-19 pandemic (49.7%). Respondents who have donated blood so far still mostly want to donate blood after the pandemic (90%), among those who have not done so 38% want to do so after the pandemic (p < 0.001). The vast majority of respondents believed it was safe to donate blood during the pandemic (93%), and most were aware that symptoms of infection disqualify a blood donor (83.2%). Only 43.2% knew that “Convalescents who donate plasma are entitled to a blood donation deduction”. Conclusions: The current pandemic situation is not an obstacle to donating blood. Blood donations should not be withheld unless there are health contraindications. Due to additional procedures, it is still safe to donate blood. Efforts to promote blood donation during the COVID-19 pandemic should be continued.